2023
DOI: 10.3390/ijms24119473
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctive Analyses of BSA-Seq and BSR-Seq to Identify Candidate Genes Controlling the Black Lemma and Pericarp Trait in Barley

Abstract: Black barley seeds are a health-beneficial diet resource because of their special chemical composition and antioxidant properties. The black lemma and pericarp (BLP) locus was mapped in a genetic interval of 0.807 Mb on chromosome 1H, but its genetic basis remains unknown. In this study, targeted metabolomics and conjunctive analyses of BSA-seq and BSR-seq were used to identify candidate genes of BLP and the precursors of black pigments. The results revealed that five candidate genes, purple acid phosphatase, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…We screened 3200 inbred lines from our BC 2 F 6 and TH1-7 populations using previous markers (Long et al, 2019), plus 10 newly designed indel markers (Table S1), which enabled us to position HvBlp between markers BLZK98 and MC_1570156, spanning 0.484 Mb using Morex (V3) as reference (Figure 1d). Within this genetic interval, Morex (yellow husk) contains only seven annotated genes, none of which seem to be related to melanin or anthocyanin production.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We screened 3200 inbred lines from our BC 2 F 6 and TH1-7 populations using previous markers (Long et al, 2019), plus 10 newly designed indel markers (Table S1), which enabled us to position HvBlp between markers BLZK98 and MC_1570156, spanning 0.484 Mb using Morex (V3) as reference (Figure 1d). Within this genetic interval, Morex (yellow husk) contains only seven annotated genes, none of which seem to be related to melanin or anthocyanin production.…”
Section: Resultsmentioning
confidence: 99%
“…The candidate gene controlling the black husk/pericarp trait in barley has puzzled barley researchers for a long time. Several previous studies (Bungartz et al ., 2016 ; Glagoleva et al ., 2017 , 2022 ; Jia et al ., 2017 ; Liu et al ., 2023 ; Long et al ., 2019 ; Shoeva et al ., 2016 ) have attempted to uncover its molecular basis but have all failed to date. In the present study, we identified the corresponding candidate gene HvBlp by screening an exceptionally large collection of 3200 inbred lines.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations